Overview of anthelmintic resistance of gastrointestinal nematodes of small ruminants in Brazil - Salgado,Jordana Andrioli (2016)
Abstract Frequent and inappropriate use of all classes of antiparasitic drugs in small ruminants has led to failures in their effectiveness, culminating in a global problem of anthelmintic resistance. Brazil stands out as one of the world’s leaders in publications about anthelmintic resistance, and for having the most numerous reports of this resistance in small ruminants in the Americas. These studies have involved mainly the fecal egg count reduction test (FECRT) and its correlation with field management practices. In vivoeffectiveness testing is conducted in areas where livestock is of greater economic significance, e.g., in the South (sheep) and Northeast (goats), or is important for research and economic centers, such as the Southeast (sheep). The most widely studied species is sheep, for which the widest range of drugs is also evaluated. Despite significant advances achieved in molecular research, laboratory analyses should include knowledge about the reality in the field so that they can become feasible for the producer. Moreover, molecular studies can be underpinned by the analysis of field studies, such as the maintenance of antiparasitic effectiveness over time and the mechanisms involved in this process.